2015
DOI: 10.1093/abbs/gmv058
|View full text |Cite
|
Sign up to set email alerts
|

IL-37b suppresses T cell priming by modulating dendritic cell maturation and cytokine production via dampening ERK/NF-κB/S6K signalings

Abstract: Interleukin 37b (IL-37b) plays a key role in suppressing immune responses, partially by modulating the function of dendritic cells (DCs). However, the precise mechanisms are still largely unknown. Here, we investigated the effects of IL-37b on DC maturation and T cell responses induced by DCs, and explored the involved signaling pathways. It was found that IL-37b down-regulated the expressions of co-stimulatory molecules CD80 and CD86 on DCs in vitro. At the same time, the expressions of pro-inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 28 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have reported that dendritic cells could produce IL-37 22 and also is target cells of IL-37 23 . Thus, the effects of the IL-37V1 allele as a key regulator of IL-1β are further investigated using human dendritic cells from homozygous IL-37V1, as compared to IL-37WT individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that dendritic cells could produce IL-37 22 and also is target cells of IL-37 23 . Thus, the effects of the IL-37V1 allele as a key regulator of IL-1β are further investigated using human dendritic cells from homozygous IL-37V1, as compared to IL-37WT individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The function of DCs can be impaired via multiple pathways. Interleukin (IL) 37b, a protein with a critical role in the inhibition of the innate immune response, suppresses DC maturation and function by decreasing CD80 and CD86 expression via the ERK/S6K/NF-kB signaling pathways (45). Furthermore, DC maturation and tumor infiltration increased significantly in melanoma following the inhibition of signal transducer and activator of transcription 3 (STAT3), a transcription factor that is required for tumor growth and metastasis (46).…”
mentioning
confidence: 99%
“…is most probably not determinant in the control of lentivirus infection. In addition, IL37 was reported to suppress antigen-specific adaptive immunity via the induction of tolerogenic dendritic cells 45 , and to inhibit T-cell priming by modulating dendritic cell maturation 61 .…”
Section: Discussionmentioning
confidence: 99%